If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11x+x+3=4(x-2)+8x+11
We simplify the equation to the form, which is simple to understand
11x+x+3=4(x-2)+8x+11
Reorder the terms in parentheses
11x+x+3=+(+4x-8)+8x+11
Remove unnecessary parentheses
+11x+x+3=+4x-8+8x+11
We move all terms containing x to the left and all other terms to the right.
+11x+1x-4x-8x=-8+11-3
We simplify left and right side of the equation.
0x=0
0=0
This equation is an identity, so all real numbers are solutions.
| 9x-2=2x | | 3y-9=0+3 | | 3m=5.7 | | .4x-9=.1(x+30) | | -1=u-2 | | 52=-2(22-x)+4(x-3) | | 32x^2+18=0 | | (a+1)*(a-3)x=(a+1)*(a+4) | | .8(220-a)=120 | | 2(1+v)=-6+4v | | 117+7y=180 | | 9x^2-18xy-8x+16y=0 | | 15n-6n= | | 3s+s=-49 | | -9.8(27x-65)=78.24(6x+34) | | 4(x-5)-2(x+2)=-22 | | 3e-4=-2 | | 2+14a=-8+9a | | 7y+18=180 | | 60x^2-20xy+12x=0 | | -7(a-6)=2-2a | | 4(x-3)=2x+2(x-6) | | 2x^6-17x^4+17x^3= | | 15x+45=180 | | ba-4b=c | | .5x+3=2 | | 6x^3-9x^2-216x+9=0 | | 25=-8+2(s-4) | | 3(a+b)=f | | 35x^2-9x-2=0 | | (-6x+7)=(19x-1) | | 9y+4-7y=124 |